Building Numerical Literacy for Prospective Mathematics Teachers Through Analogical Reasoning - Mutia Mutia; Kartono Kartono; Masrukan Masrukan; Dwijanto Dwijanto; Kristina Wijayanti (International Conference on Science, Education, and Technology, 2021)
The purpose of this study is to analyze how analogical reasoning as one of the reasoning in mathematics can build the numeracy literacy of prospective mathematics teachers. Qualitative methodology was used in this recent study. Data collection techniques in this study are test, observation, interview, and documentation. Meanwhile, data analysis was processed by reducing data, presenting data, and drawing conclusions. Analogous reasoning is one way that can be used in learning to build numeracy literacy because, with analogical reasoning, students will try to find problems that are similar to the questions given and then learn them by reading and understanding the information it provides. However, analogous reasoning in research can only be done by students with high abilities, while students with low abilities have not been able to use this reasoning. Nowadays, reasoning is very mandatory to use in literacy-based learning because literacy requires reasoning, without reasoning, it will be difficult for students and prospective teachers to be able to solve numeracy literacy questions.